2019
DOI: 10.1016/j.biombioe.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic temperature evaluation of macauba biochar for uranium adsorption from aqueous solutions

Abstract: This study aims to evaluate the effect of the pyrolytic temperature on the biochar derived from the macauba endocarp for the removal of uranium (VI) from aqueous solutions. The endocarp was subjected to six different pyrolytic temperatures, ranging from 250 ºC to 750 ºC. The biochars obtained at each temperature were evaluated for their adsorption capacities ("q"). The highest adsorption capacities were obtained for the biochar produced at 250 ºC (BC250), followed by the one obtained at 350 ºC (BC350), with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…3 ) indicated that the SS material has more H relative to FC, while the biochar produced at high pyrolysis temperatures has less H relative to FC. Working with biochar derived from macaúba endocarp pyrolyzed at temperatures from 200 to 700 °C 56 , reported a similar relationship between H/C and FC. The reduction in the H/C ratio at higher temperatures also results from the breakup of oxygen-containing functional groups, such as carboxyl, carbonyl, and methoxyl, and the formation of aromatic compounds 57 .…”
Section: Resultsmentioning
confidence: 74%
“…3 ) indicated that the SS material has more H relative to FC, while the biochar produced at high pyrolysis temperatures has less H relative to FC. Working with biochar derived from macaúba endocarp pyrolyzed at temperatures from 200 to 700 °C 56 , reported a similar relationship between H/C and FC. The reduction in the H/C ratio at higher temperatures also results from the breakup of oxygen-containing functional groups, such as carboxyl, carbonyl, and methoxyl, and the formation of aromatic compounds 57 .…”
Section: Resultsmentioning
confidence: 74%
“…BC350 was selected for the preliminary experiments based on a previous study [26], in which the gravimetric yield factor was used to identify the temperature at which to obtain a biochar with the maximum fixed carbon content and gravimetric yield. In this case, the gravimetric yield obtained for BC350 was of 46.09 % and the fixed carbon content was of 60.22 %, rendering a gravimetric yield factor of 0.28 %, which, by comparison, qualified 350 °C as the operational HTT.…”
Section: Effect Of Phmentioning
confidence: 99%
“…The MB is excited under the red region of the light source and received electrons to the excited MB which produces an anion which abstracts a proton from water to provide LMB; the LMB is very readily re-oxidized back to MB if there is any oxygen in the solution [9,10,21].…”
Section: The Antibiotics Photodecomposition Productsmentioning
confidence: 99%